The information literacy levels of nursing students who take the course on information techniques (Annals of Medical Research, 2021)
Aim: This study was conducted with the purpose of determining the information literacy levels of nursing students who take the course on information techniques in nursing and those who do not. Material and Methods: This descriptive study was conducted. The population of the study consisted of the 1st and 2nd year students of a school of nursing located in Eastern Turkey. The study was completed with 265 students. A personal information form and an information literacy scale were used to collect the data.Results: In the study, it was found that the mean information literacy scores of the participants who took the course on information techniques in nursing and those who did not were respectively 3.92±0.6 and 3.41±0.6, and the difference between the groups was statistically significant (p0.05). The relationship between the information literacy levels of the participants and their weekly times of using the internet and levels of computer usage was significant.Conclusion: As a result of the study, it was found that taking the course on information techniques in nursing, affected information literacy to a significant extent. It is recommended to increase information and communication courses and research on this topic in the education system for nursing.
Keywords: Information literacy; information techniques; nursing